Characteristics of contaminants in the polish-origin bee products and cancer risk assessment. (May 2023) - Sawicki, Tomasz; Surma, Magdalena; Sadowska-Rociek, Anna
Abstract: The aim of this study was to evaluate the concentration of 5-hydroxymethylfurfural (HMF), furfural, polycyclic aromatic hydrocarbons (PAHs), and pesticide residues, as well as assessment of cancer risk of the Polish-origin bee products. The bee product samples were prepared using a modified QuEChERS method, then PAHs and pesticides were analysed by gas chromatography-mass spectrometry (GC-MS), neonicotinoids by high-performance liquid chromatography with a diode array detector (HPLC-DAD), and HMF and furfural by spectrophotometry (HPLC-UV/Vis). The results showed that the highest furfural content was found in bee bread from the northeast part of Poland; moreover, samples obtained from the same region were also characterized with a higher level of HMF. The total sum of PAHs ranged from 324.0 to 866.4 μg/kg; the highest content of PAH4 (the sum of benzo[a]anthracene, chrysene, benzo[b]fluoranthene and benzo[a]pyrene) was 21.0 μg/kg, but only benzo[a]anthracene and chrysene were detected in the samples. Imidacloprid and acetamiprid were found only in bee bread from the northeast part of Poland, while clothianidin was detected in honey samples. The acceptable cancer risk has been calculated for PAHs due to ingestion of honey, while increasing the risk of cancer was calculated for bee bread and bee pollen. Due to the high concentration of PAHs and excessively high recommended consumption dose, regular consumption of bee bread and pollen may pose a severe threat to human health and should be strictly limited. Highlights: Content of contaminants varied significantly across bee products. Beeswax was characterized by the highest total PAHs concentration. The PAHs in bee products come from petro- and pyrogenic combustions. The cancer risk assessment of bee products depends on the concentration of PAHs.